Monitoramento de transporte de sedimento e avaliação de perdas de solo em uma microbacia no ecótono Cerrado-Amazônia - Sirqueira, Evellynn Sato (2022)
Among the environmental impacts observed over the years, soil erosion and river sedimentation stand out. Therefore, it is important to carry out the hydrosedimentological study of hydrographic basins, and with the help of prediction models it is possible to obtain the production of sediments, which makes it possible to minimize the costs of monitoring in the field, and also enabling the prediction of alternative environmental scenarios. . In this way, the research sought to evaluate the production of sediments in the Caiabi river microbasin, inserted in the transition between the Amazon forest and the Cerrado. When verifying an overestimation of sediment production using the original location coefficients of the MUSLE mathematical model, the model was calibrated and validated using solid key curve data obtained by field measurements, and with the use of three different methodologies in obtaining new values for a and b, in which it was verified that the best fits were obtained by the method of least squares. In this research, the liquid flows, the suspended concentrations and the turbidity values were also determined in one of the sections of the study basin and, when performing the statistical evaluation, good adjustments were observed for the net rating curve. The same occurred when relating the solid discharge with the flow and concentration of suspended sediments. As for the turbidity data, good results were observed when related to the concentration of suspended sediments, but when performing the correlation with the solid discharge, it did not present a good fit in one of the analyses.